1973
DOI: 10.1136/gut.14.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative colitis and carcinoma of the proximal bile ducts

Abstract: SUMMARY In a review of 103 patients with carcinoma of the proximal bile ducts, eight patients were noted to have had ulcerative colitis also. This finding is strongly suggestive of a specific association between the two diseases. In three of the patients, carcinoma developed several years after proctocolectomy. Seven of the eight patients were significantly younger than the median age of the group as a whole, but no other apparent difference was noted between those with ulcerative colitis and the remainder of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…Most previous reports have concluded that gallstones, which have been proposed as a definite risk factor for carcinoma of the gallbladder (16), were not a causative factor for cholangiocarcinoma (7,17). Cholelithiasis was observed in 30% to 48.1% of patients with cholangiocarcinoma, and in particular, choledocholithiasis was present in 18.5% to 21.2% of patients with extrahepatic cholangiocarcinomas (13,14,17), which was a surprisingly high incidence. Choledocholithiasis is generally classified as originating from two areas, that is, the bile duct and the gallbladder.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most previous reports have concluded that gallstones, which have been proposed as a definite risk factor for carcinoma of the gallbladder (16), were not a causative factor for cholangiocarcinoma (7,17). Cholelithiasis was observed in 30% to 48.1% of patients with cholangiocarcinoma, and in particular, choledocholithiasis was present in 18.5% to 21.2% of patients with extrahepatic cholangiocarcinomas (13,14,17), which was a surprisingly high incidence. Choledocholithiasis is generally classified as originating from two areas, that is, the bile duct and the gallbladder.…”
Section: Discussionmentioning
confidence: 98%
“…The overall incidence of cholangiocarcinoma associated with hepatolithiasis is 2.4% to 5.0% (8)(9)(10)(11)(12), and many past reports have suggested that hepatolithiasis-induced chronic bile stasis and bacterial infection may be important etiologic factors for cholangiocarcinoma. On the other hand, although cholelithiasis has been observed in 30% to 48.1% of patients with cholangiocarcinoma (13,14), a definitive cause-and-effect relationship between cholangiocarcinoma and cholelithiasis has not been established.…”
mentioning
confidence: 92%
“…The remaining 28 patients had either direct regional invasion (2 1) or hematogenous distant metastases (7). At diagnosis, tumor involvement was detected in the liver (13), periductal lymph nodes (12), gallbladder (7), pancreas (3), colon (2), duodenum (I), stomach (l), and bone marrow (1). The anatomical location of the tumor in the biliary system was limited to hepatic, common hepatic, or cystic duct in 20 patients, and located in the common bile duct in 27 patients.…”
Section: Laboratory and Radioisotopic Findingsmentioning
confidence: 99%
“…Although this tumor is considered to have biologic properties that might make it an ideal lesion for resection, resectability rates are generally low [3]. However, resection rates of up to 50% of lesions have been reported with very encouraging results for long-term survival [4].…”
Section: Bile Duct Cancer (Cholangiocarcinoma)mentioning
confidence: 99%